Longitudinal clinicopathological follow up of breast cancer patients from 1988 to 1996 in Jakarta - Tjindarbumi, Didid; Tjahjadi, Gunawan; Ramli, Muchlis; Ohno, Yoshiyuki; Darwis, Idral; Sakamoto, Goi; Cornain, Santoso; Soetrisno, Esti; Prihartono, Joedo; Roostini, Endang S.; et al. (Medical Journal of Indonesia, 1999)
[no abstract available]